Surgical treatment of different types of endometriosis: Comparison of major society guidelines and preferred clinical algorithms. (August 2018) - Kho, Rosanne M.; Andres, Marina Paula; Borrelli, Giuliano Moysés; Neto, Joao Siufi; Zanluchi, Alan; Abrão, Mauricio Simões
Abstract: Treatment options for patients with different types of endometriosis – superficial, ovarian, or deep – vary depending on the clinical presentation. New findings in the recent years regarding the role of preoperative imaging, efficacy of medical therapy, and effect of surgery on ovarian reserve have changed the way we understand the disease and subsequently the way we treat our patients. Practicing clinicians frequently refer to published recommendations from major societies for treatment guidelines. This paper aims to present and compare the varying major society guidelines on the indications and best surgical treatment approach for the management of the different types of endometriosis. We also present our preferred surgical treatment algorithm given the evidence in the literature and our cumulative 30-year clinical experience in a large tertiary referral center. Highlights: Surgical resection of endometriosis is may improve fertility outcomes and pain symptoms, however there is limited data when to indicate surgery. Surgery for ovarian endometriosis can impact in ovarian reserve, therefore critical factors should be considered. There are no specific guidelines regarding the type of procedure to be performed for deep endometriosis.